Sistem Informasi dan Pelayanan Kasus Emergency Menghadapi Kuliah Offline Pasca Pandemi Covid-19 - Jasmin Ambas; Meliana Handayani (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2023)
Campus is a potential place to become the epicenter of Covid-19 transmission from students, lecturers, employees and the general public. This paper aims to formulate and design problem solutions to guide information systems and emergency case services, including Covid-19. This paper is a qualitative approach through deepening emergency theory including Covid-19 cases, objective conditions of campus life based on patient safety principles, especially acute disease attacks (heart attacks, strokes and accidents, disasters) including Covid-19 cases with a new variant whose virulence is said to be more dangerous, faster and more deadly without any signs and symptoms. Hence, it requires emergency services so as not to cause casualties, disability or even death. The results of the research show that the campus does not yet have an information system and service mechanism if an emergency case occurs at any time. The model for formulating information system design and emergency case services in the campus environment is (1) establishment and management arrangement of the information system management unit for disaster services and emergency cases; (2) Preparing an information system program (3) Preparing Standard Operating Procedures for disaster and emergency case service systems and (4) Preparing human resources for unit management.